Peran Akuntansi Terhadap Efektivitas Pengendalian Keuangan Pondok Pesantren (Al-Islam Gorontalo) - Hamsil Hamdi (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
The role of accounting in Islamic boarding schools is very important, because the ability to provide various information and answers related to all kinds of financial activities can have a positive impact on the public sector, especially Islamic boarding schools. For this reason, with the presence of Islamic boarding school accounting guidelines compiled by Bank Indonesia in collaboration with the Indonesian Accounting Association, of course, it is hoped that boarding school administrators can study these guidelines, so that they are able to control financial records in Islamic boarding schools